An interactive tool for developing distributed telemedicine systems - V. P. Guskov; D. E. Gushchanskiy; N. V. Kulabukhova; S. A. Abrahamyan; S. G. Balyan; A. B. Degtyarev; A. V. Bogdanov (Компьютерные исследования и моделирование, 2015)
Getting a qualified medical examination can be difficult for people in remote areas because medical staff available can either be inaccessible or it might lack expert knowledge at proper level. Telemedicine technologies can help in such situations. On one hand, such technologies allow highly qualified doctors to consult remotely, thereby increasing the quality of diagnosis and plan treatment. On the other hand, computer-aided analysis of the research results, anamnesis and information on similar cases assist medical staff in their routine activities and decision-making. Creating telemedicine system for a particular domain is a laborious process. Its not sufficient to pick proper medical experts and to fill the knowledge base of the analytical module. Its also necessary to organize the entire infrastructure of the system to meet the requirements in terms of reliability, fault tolerance, protection of personal data and so on. Tools with reusable infrastructure elements, which are common to such systems, are able to decrease the amount of work needed for the development of telemedicine systems. An interactive tool for creating distributed telemedicine systems is described in the article. A list of requirements for the systems is presented; structural solutions for meeting the requirements are suggested. A composition of such elements applicable for distributed systems is described in the article. A cardiac telemedicine system is described as a foundation of the tool